Regulating the Vehicle Speed in Accident Prone Zones Integrated with Effective Parking Management System - R., Joseph Amalan J; P., Darwin; S., Ram Prakash; R., Indhu; S., Annie Angeline Preethi (Journal of ISMAC, 2025)
Speed levels of road crashes and traffic offenses in restricted areas, such as residential areas, health centers, and schools, require the application of appropriate measures to ensure speed automation. This paper describes the design and development of an automatic speed control device for vehicles utilizing Zigbee technology for control and real-time monitoring. The focal point of the system is a microcontroller and Zigbee communication modules in both directions, from the vehicle to surveillance devices installed within the restricted area. Zigbee network data transmission and reception facilitate efficient monitoring of speed and control. The speed of a vehicle as it enters the restricted area is automatically decreased to the designated limit without any human intervention. Effectiveness in the system is achieved through simulation and actual field testing, which have been proven to be effective, responsive, and reliable in enhancing road safety in high-impact areas. The technology is functional and scalable, providing a robust solution for avoiding speed-related crashes, which are crucial in traffic management systems. Smart parking solutions detect vacant parking spaces in real time using sensors and inform drivers via a virtual screen or mobile app. This reduces wasteful parking search time, is easy to install, and promotes efficient space utilization. It is based on IoT technologies and data processing, ensuring efficient and accurate operation. In this system, time and fuel are saved, and traffic is reduced.
Keywords: Zigbee Technology; Vehicle Speed Regulation; IoT Technologies; Sensors